Parental Psychological Distress Moderates the Impact of a Video Intervention to Help Parents Manage Young Child Vaccination Pain. (17th August 2018) - Gennis, Hannah; Pillai Riddell, Rebecca; O'Neill, Monica C; Katz, Joel; Taddio, Anna; Garfield, Hartley; Greenberg, Saul
Abstract: Objective: The current study sets out to conduct a post hoc analysis of the moderating effect of parent psychological distress on a pediatric pain management intervention. Methods: Parents of 6-month-old infants ( n =  64) and 18-month-old toddlers ( n  =   64 each) were randomized to a treatment (The ABCDs of Pain Management) or control video and videotaped during the vaccination. Parent psychological distress was also measured at the vaccination. Outcomes were children's pain, parent worry, and parent soothing behavior post-vaccination. Results: Parent psychological distress only moderated video effect on toddler pain during the regulation phase. Parent psychological distress did not moderate the impact of the video on parent worry or parent soothing post-needle at either age. The video did increase parent soothing in parents of both infants and toddlers, and reduced worry in parents of toddlers. Conclusions: To our knowledge, this is the first study to assess a moderating factor on a child pain management intervention. The video's efficacy was moderated for toddlers' pain regulation, such that parents with high psychological distress did not show as much benefit from the intervention. No other moderations were found in either age group for any other outcome. Main effects for the video impacting soothing behavior of parents of both infants and toddlers were confirmed, and a new finding of video efficacy was seen through the significantly lower worry of toddlers' parents post-needle. Given the nonclinical sample, low levels of psychological distress were found. Efforts to replicate this study in a higher risk sample are necessary.